2021
DOI: 10.1037/lat0000163
|View full text |Cite
|
Sign up to set email alerts
|

The undocumented advantage: Intersectional predictors of critical consciousness and academic performance among U.S. Latinxs.

Abstract: The success of U.S. Latinxs in higher education remains low compared to other racial/ ethnic groups, likely due in part to systemic barriers and social oppression that differentially impact Latinxs based on immigration status, social class, gender, and age. We developed a testable model guided by Latinx critical theory (Delgado & Stefancic, 2000) and undocumented critical theory (Aguilar, 2019) to operationalize how immigration status, social class, gender, and age may serve as predictors of critical conscious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Research is finding that immigration status also intersects with other social determinants of health to further restrict the well-being of immigrants (H. Castañeda et al, 2015), particularly among Latinx (Cabral & Cuevas, 2020). For instance, a recent study found that immigration status was associated with lower income, and that lower income mediated the link between immigration status and educational attainment among Latinx students (Cadenas & Kiehne, 2021). That same study found that immigration status was linked to other social positions where immigrants may experience disadvantage, such as income, gender, and age, and that these social conditions, in turn, predicted their educational outcomes.…”
Section: Immigration/immigrant Statusmentioning
confidence: 99%
“…Research is finding that immigration status also intersects with other social determinants of health to further restrict the well-being of immigrants (H. Castañeda et al, 2015), particularly among Latinx (Cabral & Cuevas, 2020). For instance, a recent study found that immigration status was associated with lower income, and that lower income mediated the link between immigration status and educational attainment among Latinx students (Cadenas & Kiehne, 2021). That same study found that immigration status was linked to other social positions where immigrants may experience disadvantage, such as income, gender, and age, and that these social conditions, in turn, predicted their educational outcomes.…”
Section: Immigration/immigrant Statusmentioning
confidence: 99%
“…Given evidence that “privilege checking” is associated with diverging outcomes for people in different social locations (Egan Brad et al, 2019), efforts to incorporate understanding of privilege and oppression should be grounded in the evidence base. In a recent study, Cadenas and Kiehne (2021) integrated Intersectionality, LatCrit, and UndocuCrit in a model to predict CC and academic performance among undocumented Latinx students and U.S. citizens. They found that indeed, identification with groups experiencing greater marginalization (i.e., undocumented immigrants, older age, lower income, and female) was predictive of greater CC, and higher achievement in turn.…”
Section: A Vision For Promoting Critical Consciousness Within Vocatio...mentioning
confidence: 99%
“…Research has also more broadly operationalized notions of vocational hope and work hope through social cognitive and racial identity development frameworks, as well as through measurement of its underlying components (i.e., goals, agency, and pathways; Jackson & Neville, 1998;Juntunen & Wettersten, 2006;Brown et al, 2013). Similarly, the construct of political outcome expectations may tap onto some dimensions of critical hope, and these outcome expectations have been found to result from the interplay between reflection and action (Cadenas et al, 2018(Cadenas et al, , 2020a(Cadenas et al, , 2021. Evidently, there is great promise and cultural relevance in further operationalizing critical hope in vocational psychology research, career development intervention, and policy.…”
Section: Clarifying Formation Of Critical Consciousnessmentioning
confidence: 99%
“…This perception may also be stronger for Latinx youth from low socioeconomic backgrounds because of the higher value placed on education improving one’s life (Rivas-Drake, 2008; Toyokawa & Toyokawa, 2019). The Latinx immigrant experience includes hardships in education (e.g., linguistic barriers, socioeconomic barriers, lack of navigational capital; Yosso, 2005), which build a critical consciousness among Latinx emerging adult college students to be more engaged and resilient as they work toward their educational pursuits (Cadenas & Kiehne, 2021). Consistent with Social Cognitive Theory, however, gendered socialization and cultural ties to the country of origin (via immigrant generation) suggest that socialization and experiences of familismo are not uniform for all Latinx adolescents and emerging adults.…”
Section: Introductionmentioning
confidence: 99%